RDNA-05. RADIOTHERAPY PROMOTES ONCOPROGRESSIVE CROSSTALK BETWEEN GLIOBLASTOMA TUMOR CELLS AND M2 MACROPHAGES VIA THE NLRP3 INFLAMMASOME PATHWAY. (11th November 2019) - An, Shejuan; Rooney, Michael K; Miska, Jason; Lee Chang, Catalina; Zhang, Peng; Han, Yu; Lopez-Rosas, Aurora; Lesniak, Maciej S; Sachdev, Sean
Abstract: PURPOSE: Radiotherapy (RT) is an essential component in the adjuvant treatment of glioblastoma (GBM); however, despite an initial benefit in tumor control, recurrence is nearly universal. The inflammasome is a multimeric cytosolic complex that has been shown to be activated in immune cells following RT. We investigated the relationship of inflammasome activation and disease progression after RT in GBM. METHODS: We performed survival analysis for patients with recurrent GBM using the TCGA dataset, stratifying according to expression of inflammasome pathway molecules Caspase 1 (CASP1), IL-1β, and NLRP3. IL-1β expression and colocalization with CD11b + myeloid cells were analyzed at different time points following RT in a murine glioma GL261 model. We detected the secreted IL-1β, CASP1 activity, and NLRP3 expression in both tumor and infiltrating immune cells, and the downstream effects of their interplay, including cellular apoptosis, proliferation, and viability. RESULTS: High expression of CASP1, IL-1β, and NLRP3 are associated with poor survival in recurrent GBM. In a mouse model, recurrent tumors after treatment with RT display higher levels of the inflammasome effector molecule IL-1β, which colocalizes with infiltrating CD11b + myeloid cells. Using a co-culture system of tumor cell and M2 macrophages, we found that RT enhances inflammasome activation in both cell types, and this interaction restores the proliferative capacity of surviving tumor cells following treatment. RT induces the inflammasome pathway activation in the setting of an associated immune microenvironment rich in tumor-associated macrophages and myeloid-derived suppressor cells (TAM/MDSCs) and not in tumor cells alone. CONCLUSIONS: Inhibition of the oncoprogressive crosstalk between GBM tumor cells and M2 macrophages, possibly through disruption of the inflammasome pathway, might be a potential therapeutic strategy with RT.